Pelatihan Hype Virtual Reality Di SMA Muhammadiyah 1 Surakarta - Aisyah Mutia Dawis (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Nowadays, technology is becoming more advanced and modern. This training includes an introduction to the basic concepts of VR, the hardware and software used, and effective VR content creation techniques. The training method is an offline class. During the training, participants will be taught effective VR content creation techniques, such as 3D modeling, animation, lighting, and sound adjustment. Participants will also be taught about the layout of VR content and the use of effective user interaction. After completing the training, participants are expected to be able to create quality and effective VR content, as well as understand how to customize VR content to the goals and target users. With the increasing interest and demand for VR content, VR creation training is becoming increasingly important to help improve the skills and abilities of individuals in the VR industry.